Pelatihan Metodologi Penelitian Analisis Data Menggunakan Microsoft Excel dan SPSS di STIE Tribhakti Bekasi - Sitinjak, Tumpal J R (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Carrying out research is an obligation carried out by lecturers and students at universities. However, a good research implementation must of course be supported by an understanding of research methodology and the use of available and qualified data processing program applications. The results of interviews conducted by the community service team of the Institute of Business and Informatics Kwik Kian Gie indicate that thesis supervisors and students who compose theses at STIE TRIBHAKTI Bekasi really need training related to understanding research methodologies and using data processing programs in this case Excel and SPSS and how interpret the output of the processed results. Based on this background, a training on research methodology and data analysis using Excel and SPSS was held on Saturday, March 31, 2021 at 13.30 – 16.30. This activity is carried out online using Google Meet virtual media. The material presented includes univariate, bivariate, multivariate, and path analysis. One part of multivariate analysis is multiple regression. After the training was given, the thesis supervisors and students who wrote the thesis at STIE TRIBHAKTI benefited from increasing knowledge and understanding of research methodology and becoming more skilled in using Microsoft Excel and SPSS data processing applications, so that this can be a motivation that moves lecturers and students to do research well.